Specification for phenol - British Standards Institution (London BSI, 1964)
Phenol, Phenols, Solubility, Solubility test methods, Crystallization, Boiling point, Temperature measurement, Samples, Determination of content, Water content determination, Chemical analysis and testing, Evaporation residue determination, Test equipment, Sampling methods
Withdrawn
Cross References BS 458/1, BS 458/4, BS 479/3, BS 572, BS 593, BS 604, BS 616, BS 756, BS 846, BS 1583, BS 1792, BS 2735
Keywords: Phenol -- Standards